1998
DOI: 10.1074/jbc.273.39.25198
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor p53 as a Component of the Tumor Necrosis Factor-induced, Protein Kinase PKR-mediated Apoptotic Pathway in Human Promonocytic U937 Cells

Abstract: Despite what is known about the early signaling events in tumor necrosis factor (TNF) ␣-induced apoptosis, characterization of the downstream events remains largely undefined. It is now known that a crosstalk exists between the interferon and TNF-␣ pathways. This linkage allows recruitment of the cell proliferation suppressor PKR (dsRNA-dependent protein kinase) from the interferon pathway to play a pivotal role in TNF-␣-induced apoptosis. In this study, we took advantage of the differential TNF-␣ susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 29 publications
2
54
1
Order By: Relevance
“…It has been proposed that PKR mediates apoptosis at the transcriptional level. For example, PKR signals through STAT1 and STAT3 (36,43,44), interferon regulatory factor 1 (IRF1) (16,45), IRF3 (46), p53 (17,47,48), and the IKK complex to regulate transcription during proinflammatory (16,17,40,45) and/or proapoptotic responses (12,40,45,49). PKR-dependent apoptosis was also associated with Fas-associated death domain (FADD)-mediated activation of caspase 8 (50,51) and up-regulation of Fas and Bax (18,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that PKR mediates apoptosis at the transcriptional level. For example, PKR signals through STAT1 and STAT3 (36,43,44), interferon regulatory factor 1 (IRF1) (16,45), IRF3 (46), p53 (17,47,48), and the IKK complex to regulate transcription during proinflammatory (16,17,40,45) and/or proapoptotic responses (12,40,45,49). PKR-dependent apoptosis was also associated with Fas-associated death domain (FADD)-mediated activation of caspase 8 (50,51) and up-regulation of Fas and Bax (18,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that TNF-induced cell proliferation was significantly suppressed by PKR deletion. Although PKR is known to mediate TNFinduced apoptosis in certain cells (Yeung and Lau, 1998), its role in TNF-induced proliferation of cells is not known. The difference in results may be owing to cell types used; human myeloid U-937 cells used by Yeung and Lau (1998) may have multiple genetic defects, as compared to PKR-deleted MEF used in our studies.…”
Section: Role Of Pkr In Tnf Signalingmentioning
confidence: 99%
“…Although PKR is known to mediate TNFinduced apoptosis in certain cells (Yeung and Lau, 1998), its role in TNF-induced proliferation of cells is not known. The difference in results may be owing to cell types used; human myeloid U-937 cells used by Yeung and Lau (1998) may have multiple genetic defects, as compared to PKR-deleted MEF used in our studies. Consistent with our results, Donze et al (2004) showed that PKR activates a cell survival pathway through the expression of NF-kB-regulated cIAP and A20 gene products.…”
Section: Role Of Pkr In Tnf Signalingmentioning
confidence: 99%
“…Previously, interactions of these two pathways have been documented. p53 was induced during apoptosis mediated by TNF-␣ in U987 cells (43) and in MCF-7 cells (44); in both cases, the presence of wild-type p53 was shown to be essential for the cytotoxic action of TNF-␣. In ME-180 cells, TNF-␣ induced apoptosis leads to a rapid accumulation of p53 protein with no induction of p21/WAF1 (45).…”
Section: Mc3s5/mtclic Provides a Potential Downstream Link For The Tnmentioning
confidence: 99%